Elite Dynamics and Political Gamesmanship: Exploring the Modern Stage of Elitogenesis - Alexander I. Solovyev (RUDN Journal of Political Science)
According to the contemporary stage of elitist origin, elite rivalry is the primary driver of societal change. In this way, the most potent catalysts for significant inventions and politically motivated initiatives in contemporary governments are the political ploys and manipulations of elite groups. However, the ways in which the ruling circles actually carry out their duties are more closely linked to coalitional forms of political dominance that emerge at the nexus of the interests of different elite groups, a confluence of their status and unofficial connections. However, their managerial competencies have not grown as much as the population as a whole, which sets the stage for decision-making and resource allocation to become more opaque. Clarifying the true effects of these changes on the dynamics of the ruling class as well as the interactions between the state and society presents a study challenge in this setting. The use of network approaches and structural and functional research methods enables us to state that, even today, the coalition “games” in the ruling class signal the structural self-renewal of the ruling circles, bringing more autonomous (post) elite communities that control key resource allocation mechanisms while simultaneously losing their responsibility to society. This is in addition to the adjustment of political projects or ideological and political compromises in updating government strategies. In addition to enhancing the latent character of public policy development and the distance between them, their informal means of influencing public policy aim to deepen the internal differences within the ruling circles.